2017
DOI: 10.14744/anatoljcardiol.2017.7464
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of 3-D printing in cardiovascular and cerebrovascular diseases

Abstract: Objective:The application of 3-D printing has been increasingly used in medicine, with research showing many applications in cardiovascular disease. This systematic review analyzes those studies published about the applications of 3-D printed, patient-specific models in cardiovascular and cerebrovascular diseases.Methods:A search of PubMed/Medline and Scopus databases was performed to identify studies investigating the 3-D printing in cardiovascular and cerebrovascular diseases. Only studies based on patient’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 61 publications
0
61
0
2
Order By: Relevance
“…Some recent systematic reviews have shown the value of 3D printing in cardiovascular and liver diseases. A systematic review of 48 studies has summarised the findings of using 3D printed models in cardiovascular and cerebrovascular diseases, with high accuracy of 3D printing in reproducing complex cardiac anatomy and pathologies, and usefulness in both education and surgical planning (8). Another recent systematic review of 28 studies focuses on the 3D printing in congenital heart disease (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent systematic reviews have shown the value of 3D printing in cardiovascular and liver diseases. A systematic review of 48 studies has summarised the findings of using 3D printed models in cardiovascular and cerebrovascular diseases, with high accuracy of 3D printing in reproducing complex cardiac anatomy and pathologies, and usefulness in both education and surgical planning (8). Another recent systematic review of 28 studies focuses on the 3D printing in congenital heart disease (10).…”
Section: Discussionmentioning
confidence: 99%
“…Patient-specific 3D printed models based on computed tomography (CT) or magnetic resonance imaging (MRI) data have been shown to accurately replicate complex anatomical structures and pathologies when compared to original source images (2)(3)(4)7). 3D printed models can also be used to assist pre-surgical planning and simulation, improve understanding of anatomy and individual lesions (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Three‐dimensional (3D) printing technology has shown increasing use in the medical field in recent years, such as creating customised prosthetics, implants, fixtures and surgical tools, as well as reproducing patient‐specific 3D printed models for surgical preparation . In order to achieve a more comprehensive viewing of CHD, 3D physical models of the heart and blood vessels can be fabricated based on volumetric scans such as computed tomography (CT), magnetic resonance imaging (MRI) and echocardiography imaging data which allow full exploitation of the 3D potential of the scans and provide more information than conventional imaging visualisations …”
Section: Introductionmentioning
confidence: 99%
“…The applications of 3D printed cardiac models are vast in scope and include, but are not limited to: (i) assisting in diagnostics, (ii) optimizing therapeutic outputs, (iii) testing novel devices, (iv) assessing patient-specific suitability for treatments, (v) providing visualized insight for surgical procedures, (vi) allowing for performance of parametric studies on hydrodynamics, and (vii) validating computational simulations. Additionally, 3D printed cardiac models present a robust didactic and communication medium for students, patients, and the greater medical public [21,23,74]. So far, considering the requisite precision, formability, and stability of 3D printed models, current strategies for cardiovascular 3D printing in clinical practices have relied on robust, non-living manufacturing technologies.…”
Section: Cardiovascular System and Tissue Modelsmentioning
confidence: 99%
“…3D scanners, computed tomography (CT), magnetic resonance imaging (MRI) systems, and other imaging technologies, as well as computer-aided design (CAD) software, are employed to collect, draw, and digitize the complex structural information of native tissues in order to create 3D printable files, (typically stereolithography (STL) files) [16,20]. Based on a highly precise, layer-by-layer building process, 3D printing techniques have been utilized to create patient-specific models for cardiovascular surgeons to visualize anatomical structures, thus facilitating a more comprehensive understanding of tissue abnormalities and promoting better surgical procedures [2123]. For engineered active tissues/organs, 3D bioprinting is able to fabricate complex tissue architecture with spatiotemporal distribution of bioactive substances (cells, growth factors, and others) to better guide tissue regeneration [16,19,24].…”
Section: Introductionmentioning
confidence: 99%